(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2024)
This article explores the psychological approach of the family in the spiritual and moral upbringing of students. It delves into the importance of family dynamics, communication patterns, and values in shaping the ethical and spiritual development of young individuals. Drawing on psychological theories and empirical research, the article highlights the role of parents and caregivers as primary agents of moral and spiritual guidance. It also discusses the challenges families face in contemporary society and offers recommendations for promoting a supportive family environment conducive to positive moral and spiritual growth